Long non-coding RNA TUG1 mediates 5-fluorouracil resistance by acting as a ceRNA of miR-197-3p in colorectal cancer - Wang, Meng; Hu, Hanqing; Wang, Yuliuming; Huang, Quanlong; Huang, Rui; Chen, Yinggang; Ma, Tianyi; Qiao, Tianyu; Zhang, Qian; Wu, Hongyu; Chen, Qingmin; Han, Dong; et al. (Journal of Cancer, 2019)
One major reason for the failure of advanced colorectal cancer (CRC) treatment is the occurrence of chemoresistance to fluoropyrimidine (Fu)-based chemotherapy. Accumulating evidence indicates that long non-coding RNAs (lncRNAs) play a critical role in cancerous processes as either oncogenes or tumor suppressor genes. Here, we observed lncRNA TUG1 was associated to the 5-Fu resistance in colorectal cancer. Firstly, quantitative analysis indicated that TUG1 was significantly increased in recurrence CRC patient samples. Kaplan-Meier survival analysis indicated that high TUG1 expression in CRC tissues was significantly associated with a higher rate of disease progression. TUG1 knockdown re-sensitized the 5-Fu resistance in colorectal cancer cells, which were 5-Fu-resistant colorectal cell line. Furthermore, bioinformatics analysis showed that miR-197-3p could directly bind to TUG1 suggesting TUG1 might work as a ceRNA to sponge miR-197-3p. Extensively, our study also showed that TYMS was the direct target of miR-197-3p in CRC cells. Taken together, our study suggests that TUG1 mediates 5-Fu resistance in CRC via miR-197-3p/TYMS axis.